Allografts for partial meniscus repair: an in vitro and ex vivo meniscus culture study - Dabaghi, Mohammad; Eras, Volker; Kaltenhaeuser, Daniel; Ahmed, Norus; Wildemann, Britt (Frontiers in Bioengineering and Biotechnology, 2023)
The purpose of this study was to evaluate the treatment potential of a human-derived demineralized scaffold, Spongioflex® (SPX), in partial meniscal lesions by employing in vitro models. In the first step, the differentiation potential of human meniscal cells (MCs) was investigated. In the next step, the ability of SPX to accommodate and support the adherence and/or growth of MCs while maintaining their fibroblastic/chondrocytic properties was studied. Control scaffolds, including bovine collagen meniscus implant (CMI) and human meniscus allograft (M-Allo), were used for comparison purposes. In addition, the migration tendency of MCs from fresh donor meniscal tissue into SPX was investigated in an ex vivo model. The results showed that MCs cultured in osteogenic medium did not differentiate into osteogenic cells or form significant calcium phosphate deposits, although AP activity was relatively increased in these cells. Culturing cells on the scaffolds revealed increased viability on SPX compared to the other scaffold materials. Collagen I synthesis, assessed by ELISA, was similar in cells cultured in 2D and on SPX. MCs on micro-porous SPX (weight >0.5 g/cm3) exhibited increased osteogenic differentiation indicated by upregulated expression of ALP and RUNX2, while also showing upregulated expression of the chondrogen-specific SOX9 and ACAN genes. Ingrowth of cells on SPX was observed after 28 days of cultivation. Overall, the results suggest that SPX could be a promising biocompatible scaffold for meniscal regeneration.